2021
DOI: 10.1109/jlt.2021.3069186
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Multiuser MIMO for LiFi in Industrial Wireless Applications

Abstract: We present a concept for networked optical wireless communications, also denoted as LiFi, to meet the requirements of industrial wireless applications. These are primarily mobility support with moderate data rates per device, reliable real-time communication and integrated positioning. We describe a distributed multiuser multiple-input multiple-output architecture, serving mobile devices via an optical wireless infrastructure. The system consists of a central unit, being connected to a number of distributed op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…In [25] it was demonstrated that, by using D-MIMO, the performance is improved and a higher data rate is achievable because the channel matrix is well-conditioned. In [5], [23], [26] and [27], a D-MIMO architecture for LiFi was investigated and its performance evaluated. It uses a coordinator, implemented as a central unit (CU) and multiple APs, also denoted as optical frontends (OFEs).…”
Section: Distributed Mimo For Lifimentioning
confidence: 99%
See 1 more Smart Citation
“…In [25] it was demonstrated that, by using D-MIMO, the performance is improved and a higher data rate is achievable because the channel matrix is well-conditioned. In [5], [23], [26] and [27], a D-MIMO architecture for LiFi was investigated and its performance evaluated. It uses a coordinator, implemented as a central unit (CU) and multiple APs, also denoted as optical frontends (OFEs).…”
Section: Distributed Mimo For Lifimentioning
confidence: 99%
“…This approach can support a higher network capacity, as well as lower latency. Here mobility is supported by implementing MIMO algorithms at the lower physical and medium access layers in the protocol stack, whereas conventional mobile networks implement those at the transport and higher layers [5]. This advanced approach aims at new services in the future Industrial Internet-of-Things (IIoT), where wired communication links will be replaced by wireless connections that, however, interfere with each other.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the feasibility of using VLC systems in industrial production environments has been examined in literature [247], [248]. In [249], [250], the performance of VLC-based systems for multi-user MIMO architectures is investigated.…”
Section: B the Owc-iott In Smart Citiesmentioning
confidence: 99%
“…These techniques consider the many links between all base stations and all mobile users as one huge distributed MIMO which coordinated by a central controller. Note that this approach enables both, higher data rates and lower latency [27]. Here, we follow this approach in order to optimize the performance.…”
Section: Distributed Mu-mimo Conceptmentioning
confidence: 99%